Precision measurements on a single trapped beryllium ion - Fairbank, David M., author; Brewer, Samuel M., advisor; Yost, Dylan, committee member; Sanner, Christian, committee member; Van Orden, Alan, committee member (Colorado State University. Libraries, 2024)
Precision laser spectroscopy of transitions in simple atoms can be used as a stringent test of many-body quantum electrodynamics (QED) calculations, or to extract subtle information about internal nuclear structure. 9Be+ is a three electron ion which has been the focus of study in ion trap and high energy beam experiments dating back several decades. We present the first measurements of the D-lines in 9Be+ using a single trapped ion, which reduced the experimental uncertainty of both the D1 and D2 transitions by an order of magnitude. A framework for characterization of systematic shifts due to effects like photon recoil and quantum interference in ion trap-based measurements of strong transitions is presented. From the D2 lineshape data, a 2P excited state lifetime was extracted with reduced uncertainty and better agreement with theory, compared to previous work. The first experimental measurement of the unresolved 2P3/2 hyperfine splittings is reported, which helped to uncover a sign error in the theoretical prediction of the 2P3/2 electric quadrupole hyperfine constant. This measurement required development of techniques to selectively isolate and measure the unresolved components, utilizing the exceptional state preparation and control available for trapped ions. The 1.25 GHz 2S1/2 ground state hyperfine splitting was measured with a relative uncertainty of 1.6×10−11 using microwave Ramsey spectroscopy and is in good agreement with previous measurements made in Penning traps at NIST. The technique can be extended to the rare isotope 7Be+, for which the current hyperfine constant uncertainty is four orders of magnitude larger. This planned measurement could enable extraction of an improved value of the 7Be nuclear Zemach radius. D-line measurements on the rare isotopes 7,10Be+ are also planned using the techniques developed for 9Be+. A comparison of the fine structure splitting across the isotope chain can be used to extract the relative nuclear charge radii or test the many-body QED contributions to theory in Li-like ions. A new ion trap was built and direct ablation loading of the ion trap from small 9BeCl2 salt deposits was demonstrated in preparation for loading the rare isotopes from evaporated aqueous solution.
Keywords: hyperfine structure; strong transitions; ion trap; beryllium